Health Education Increases Community Knowledge, Attitudes and Compliance With Covid-19 Health Protocols - Laoh, Joice Mermy; Kawung, Yuliana; Kiling, Maykel; Warouw, Herman (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Health education is a process to increase capacity in an effort to protect and maintain public health as a step in preventing the transmission of Covid-19. The media that can be used in implementing health education include: leaflets, brochures, seminars, video media, comic media, etc. that make it easier for people to understand and implement health protocols. Objective: To describe the effect of health education on people's knowledge, attitudes, and adherence to health protocols. Methods: This study uses a literature review on 5 articles by searching the Google Scholar database. The keywords used are through the analysis of the objectives, the suitability of the topic, the research methods used, the results of each article, and the limitations that occur. the journals reviewed are from 2015-2021. Results: From the results of the research reviewed, it shows that from various health education media, animated video is the most effective media because using animated videos makes it easier for respondents to understand and carry out health protocols that have an effect on changing knowledge, attitudes, and community compliance with health protocols. Conclusion: Health education improves people's knowledge, attitudes, and adherence to health protocols.